2023
DOI: 10.1093/infdis/jiad330
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Concordance Between Parents and Their Newborn Offspring: Results From the Finnish Family Human Papillomavirus Study

Abstract: Background The knowledge on vertical human papillomavirus (HPV) transmission is limited. We aimed to determine whether HPV transmission from parents to their offspring occur before or during birth. Methods Altogether, 321 mothers, 134 fathers and their 321 newborn offspring from the Finnish Family HPV study cohort were included. Parents’ genital and oral brush samples and semen samples were collected for HPV testing at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…According to Suominen et al [ 45 ], the genotype-specific PV concordance between mother and fetuses is suggestive for vertical intrauterine transmission. It has been suggested that vertical transmission to calves may be linked to the maternal viral load and the higher the viral load is, the higher the risk of its vertical transmission [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Suominen et al [ 45 ], the genotype-specific PV concordance between mother and fetuses is suggestive for vertical intrauterine transmission. It has been suggested that vertical transmission to calves may be linked to the maternal viral load and the higher the viral load is, the higher the risk of its vertical transmission [ 46 ].…”
Section: Discussionmentioning
confidence: 99%